ANALYSIS OF READING MATERIALS IN TEXTBOOK FOR GRADE XI SENIOR HIGH SCHOOL - Nisha Tita Mutiarni and Tiarnita Maria Sarjani Siregar (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2016)
This study aims to find out the GI and LD level, the text which has the highest GI and LD and what make the text has the highest GI and LD of Advanced Learning English 2 textbook. This study was conducted by using qualitative research. The data of study were the 18 texts inside of the Advanced Learning English 2 textbook for grade XI Senior High School. The data were analyzed by using Eggins (2004) theory. The result of this study: 1) GI level of text was high based on Eggins theory that the texts had more complex clauses than simple clause. Text 1 was 0.52. Text 2 was 1.24. Text 3 was 0.84. Text 4 was 0.92. Text 5 was 1.95. Text 6 is 1.46. Text 7 was 1.03. Text 8 was 0.90. Text 9 was 1.62. Text 10 was 1.85. Text 11 was 1.64. Text 12 was 2.25. Text 13 was 2.60 Text 14 was 1.40. Text 15 was 1.80. Text 16 was 4.00. Text 17 was 1.42. Text 18 was 1.73. The LD level of text was low based on Eggins theory that the texts had more content carrying lexical item than non-content carrying lexical items . Text 1 was 0.56. Text 2 was 0.52. Text 3 was 0.52. Text 4 was 0.54. Text 5 was 0.55. Text 6 was 0.40. Text 7 was 0.42. Text 8 was 0.36. Text 9 was 0.44. Text 10 was 0.46. Text 11 was 0.44. Text 12 was 0.39. Text 13 was 0.38. Text 14 was 0.38. Text 15 was 0.42. Text 16 was 0.38. Text 17 was 0.46. Text 18 was 0.42. 2) The text had the highest GI was 4.00 within title Removing Lead from Petrol in hortatory exposition text and the text had the highest of LD was 0.56 within title Panda in report text. 3)The length of the sentence didn’t influence the grammatical intricacy of the text but the more clause complexes and content carrying lexical items could make the reader difficult to process the text.